Early exfoliation of permanent tooth in patient with hypophosphatasia. Issue 3 (December 2017) - Okawa, Rena; Miura, Jiro; Kokomoto, Kazuma; Kubota, Takuo; Kitaoka, Taichi; Ozono, Keiichi; Nakano, Kazuhiko
Abstract: Background: Hypophosphatasia (HPP) is a rare inherited skeletal disorder caused by mutations in the ALPL gene encoding tissue-nonspecific alkaline phosphatase, with early exfoliation of primary teeth due to disturbed formation of cementum often recognized as a major dental manifestation. However, reports regarding permanent teeth in HPP cases are scant. Case report: An 11-year-old boy diagnosed with childhood type HPP was referred to our hospital for exfoliation of the maxillary right central incisor. Micro-computed tomography findings of the affected tooth revealed external root resorption, enamel hypoplasia, thin dentin, and a wide pulp chamber, while disturbed cementum formation, enamel hypoplasia, dentin hypo-mineralization, and scant cementum around the enamel junction were observed by scanning electron microscopy. Conclusion: Permanent teeth may have a risk of early exfoliation as well as other structural abnormalities in HPP patients, thus longitudinal dental follow-up examinations of affected patients are required.